Screening of Abdominal Aortic Aneurysm Using Portable Transthoracic Echocardiography among Patients with Acute Coronary Syndrome - Yousef Shukha; Ofir Koren; Tsafrir Or; Yoav Turgeman; Mahmud Mahamid; Mohamed Jabaren (Cardiology Research and Practice)
Background. Abdominal aortic aneurysm (AAA) and acute coronary syndrome (ACS) share common risk factors. Objectives. To assess the abdominal aortic diameter (AAD) among patients with ACS using transthoracic echocardiography (TTE). Methods. Patients with ACS admitted to our intensive cardiac care unit from December 2013 to June 2014 were screened prospectively for AAA via AAD measurement in the subcostal TTE view. AAA was defined as an aneurysm with a transverse diameter of ≥30 mm. Results. Sixty seven patients were included. The male-to-female sex ratio was 7 : 1. The vast majority of patients were admitted due to STEMI (73%), and the rest were equally divided as NSTEMI and unstable angina. The mean patient age was 58.4 ± 10.4 years. AAD measurements were feasible in 57 patients (85%); among them, AAA was diagnosed in six patients (10.5%). The average additional time required to measure the abdominal aorta was 4 ± 1 min. All patients with AAA were men and had a higher prevalence of smoking (83.3% vs. 60.6%, p<0.003) and a lower incidence of diabetes mellitus than those without aneurysm. The prevalence of AAA tended to be related to age (12.5% in those older than 60 years and 18.7% in those older than 65 years). Conclusions. The overall prevalence of AAA is significantly high among patients with ACS and increases with age. AAA screening as a part of routine cardiac TTE can be easily, rapidly, and feasibly performed and yield accurate findings. AAD measurement in the subcostal view should be implemented as a part of routine TTE in patients with ACS.